Dietary L-Tryptophan Modulates the Hematological Immune and Antibacterial Ability of the Chinese Mitten Crab, Eriocheir sinensis, Under Cheliped Autotomy Stress - Zhang, Cong; Zhang, Qian; Song, Xiaozhe; Pang, Yangyang; Song, Yameng; Cheng, Yongxu; Yang, Xiaozhen (Frontiers in Immunology, 2018)
In pond cultures of juvenile Eriocheir sinensis, limb autotomy stress seriously affects and restricts the quality and economic benefits of aquaculture. This study was designed to evaluate the effects of dietary supplementation of L-tryptophan on E. sinensis under the cheliped autotomy stress. In the present study, 252 crabs were divided into four groups: dietary L-trp supplementation with 0.28%, 0.40%, 0.53%, and 0.70%, and their hematological immunity, antioxidant capacity, anti-stress, and antibacterial ability were evaluated after 14 days of using biochemical analysis, flow cytometry, and molecular biology techniques. First, we counted the mortality after 14 days of feeding and found that compared with other treatments, dietary supplementation of 0.53% and 0.70% L-trp significantly lowered the mortality of E. sinensis. Moreover, the total hemocyte count (THC), hemocyanin and glutathione (GSH) content, and glutathione peroxidase (GSH-Px) activity significantly increased at 7 d and 14 d with dietary supplementation of 0.53% and 0.70% L-trp, in contrast with the significant decrease in malondialdehyde (MDA) content at 14 d in the same dietary groups (P < 0.05). Next, the bacterial challenge test after 14 days of feeding showed that the THC levels, phagocytic rate, and acid phosphatase (ACP) and alkaline phosphatase (ALP) activity were significantly higher with dietary supplementation of 0.53% and 0.70% L-trp after 12 h and 24 h of Aeromonas hydrophila injection, along with a significant improvement in the antioxidant capacity (P < 0.05). Further, we measured the expression of antibacterial-related protein genes (EslecB and HSP 90) and found that they were significant up-regulated in the hepatopancreas, hemocytes, intestine, and gill in the groups with dietary supplementation of 0.53% and 0.70% L-trp after 12 h or 24 h of A. hydrophila injection (P < 0.05). Taken together, the observations in this study indicate that dietary supplementation of L-trp can enhance the antioxidant capacity and improve the hematological immune status and antibacterial ability of E. sinensis under the cheliped autotomy stress, thereby increasing the survival rate of E. sinensis under cheliped autotomy stress.